Electrohydraulic Actuator for a Soft Gripper - Park, Tongil; Kim, Keehoon; Oh, Sang-Rok; Cha, Youngsu (MARY ANN LIEBERT, INC, 2020)
There is a considerable demand to develop robots that can perform sophisticated tasks such as grabbing delicate materials, passing through narrow pathways, and acting as mediators between humans and robots. Soft robots can provide a solution for such applications. In this study, we propose an electrohydraulic gripper, which is based on electrostatic and hydraulic forces. Interestingly, the gripper generates a hydraulic force without an external fluid supply source. In addition, it achieves good compliance, because the gripper is composed of soft materials such as polyethylene film and silicone. We experimentally investigate the characteristics of the actuator of the gripper. In addition, the electrohydraulic gripper demonstrates an ability to grasp delicate materials.
Keywords: POLYMER-METAL COMPOSITES; ROBOTICS; FABRICATION; ELASTOMERS